2021
DOI: 10.3389/fmicb.2020.620626
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Crude Fructo-Oligosaccharide Preparations Using Probiotic Bacteria for the Selective Fermentation of Monosaccharide Byproducts

Abstract: Probiotics are microbes that promote health when consumed in sufficient amounts. They are present in many fermented foods or can be provided directly as supplements. Probiotics utilize non-digestible prebiotic oligosaccharides for growth in the intestinal tract, contributing to a healthy microbiome. The oligosaccharides favored by probiotics are species-dependent, as shown by the selective utilization of substrates in mixed sugar solutions such as crude fructo-oligosaccharides (FOS). Enzymatically produced cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Although L. reuteri is known to produce a bacteriocin (reutrin) bound as antimicrobial against pathogens such as E. coli, it has shown a significant increase in the growth rate and inhibitory action against bacteria when using FOS as a sole source of carbon (Manning and Gibson, 2004;Bengmark, 2005). Likotrafiti et al (2015) and Kanjan and Hongpattarakere (2017) noticed an overall decrease in S. Typhimurium and water soluble (Gibson and Roberfroid, 1995;Roberfroid, 2001;Duggan et al, 2002;Fan et al, 2021;Wongkrasant et al, 2020;Andermann et al, 2021;Zhang et al, 2021). The most common prebiotic foods include soybeans, artichokes, oats, honey, berries, asparagus, many fruits, and goat's milk (Farnworth, 2008).…”
Section: The Antagonistic Activity Of the Synbiotic Containing Lactob...mentioning
confidence: 99%
“…Although L. reuteri is known to produce a bacteriocin (reutrin) bound as antimicrobial against pathogens such as E. coli, it has shown a significant increase in the growth rate and inhibitory action against bacteria when using FOS as a sole source of carbon (Manning and Gibson, 2004;Bengmark, 2005). Likotrafiti et al (2015) and Kanjan and Hongpattarakere (2017) noticed an overall decrease in S. Typhimurium and water soluble (Gibson and Roberfroid, 1995;Roberfroid, 2001;Duggan et al, 2002;Fan et al, 2021;Wongkrasant et al, 2020;Andermann et al, 2021;Zhang et al, 2021). The most common prebiotic foods include soybeans, artichokes, oats, honey, berries, asparagus, many fruits, and goat's milk (Farnworth, 2008).…”
Section: The Antagonistic Activity Of the Synbiotic Containing Lactob...mentioning
confidence: 99%
“…Recently, there has been an attempt to identify a potentially beneficial application of Bacillus coagulan DSM1 and Bc. ( Bacillus ) subtilis YBJ in the purification of FOSs [ 14 ]. The major drawback of these organisms is their lack of efficiency in sucrose assimilation and fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its benefits for animals, low cost and convenient use [13], there is increasing interest in the use of FOS as a feed additive [14,15]. Previous studies demonstrated that FOS could improve rumen fermentation performance, food intake [16], feed utilization efficiency [17], absorption and utilization of protein [18], production performance [19] and antioxidant capacity of ruminants [20]. It also has the ability to regulate the hormone neuroendocrine axis related to fat metabolism by affecting beneficial microorganisms and their metabolites in the intestine [21].…”
Section: Introductionmentioning
confidence: 99%